Immune cells play a critical role in cytokine- and endotoxin-mediated endothelial permeability - Patricia Gogesch; Samira Ortega Iannazzo; Nicole Rupp; Joachim Rom; Markus Kreuz; Kristin Reiche; Martina Anzaghe; Zoe Waibler (PLoS ONE, 2025)
Vascular leakage (VL) is a severe pathology occurring in a broad range of scenarios, e.g., during sepsis, cytokine storms, or as side effect of immunotherapies. Its severity is underlined by the high lethality rate of 20−30% for the systemic capillary leakage syndrome. While many compounds are reported to affect endothelial cell (EC)-activation, exact mechanisms behind VL remain unclear. We analyzed activation, viability, cytokine secretion, and relative permeability of human umbilical vein endothelial cells (HUVECs) upon treatment with 16 different stimuli. Relative HUVEC-permeability was assessed in a trans-well-based leakage assay in presence or absence of human peripheral blood mononuclear cells (PBMCs). HUVEC-activation is characterized by correlating upregulation of intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1, and E-selectin, as well as production of interleukin (IL)-8, monocyte chemoattractant protein (MCP)-1, and IL-6. Strong HUVEC-activation and reduced viability was observed upon treatment with IL-1β, tumor necrosis factor (TNF)-α, a TGN1412-induced cytokine cocktail (SNTGN1412), thrombin, and lipopolysaccharide (LPS). Only thrombin, SNTGN1412, and vascular endothelial growth factor (VEGF) led to increased relative permeability, while other compounds associated with vascular leakage, including TNF-α, IL-1β, or LPS, had no direct effect on relative HUVEC-permeability. Interestingly, co-cultures with PBMCs mediated IL-1β- and LPS- but not TNF-α-induced relative HUVEC-permeability. In our study, we show that HUVEC activation upon direct stimulation does not necessarily result in increased relative permeability or massive cytokine production. Interestingly, we could demonstrate that activated HUVECs respond with a conserved pattern of markers, independent from the stimulus used. Moreover, we observed that the interplay with immune cells is critical to enhance relative HUVEC-permeability, which however depended on the stimulus applied suggesting different mechanisms of immune-mediated VL. A better understanding of VL will uncover potential treatment-targets for patients suffering from VL and help to improve safety-assessment of leakage-associated immunotherapies.